The Influence of the Project Based Learning Model on the Ability to Think Critical and Creatively in Making a Dream House Class VI Science Subject SDN Gumilir 06 - Krista Adayu; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This research aims to 1) Analyze the stages of the PjBL learning model in making a dream house on students' critical and creative thinking skills; 2) Analyze the influence of the PjBL learning model in making dream houses on students' critical and creative thinking skills. Quantitative type of research with nonequivalent control group design and posttest only control group design. Data collection techniques use interviews, observation and tests. Meanwhile, the data analysis technique used is prerequisite testing and hypothesis testing using the t-test. The population in this study were all class VI students at SD Negeri Gumilir 06, and samples were taken randomly from two classes, namely the experimental class which used the PjBL learning model and the control class which used conventional methods. The results of the research are 1) the stages of critical and creative thinking skills using the PjBL learning model in making the dream house electrical circuit are start with the essential question, design a plan for the project, create a schedule, monitor the students and the progress of the project, assess the outcome, and evaluate the experience; 2) the PjBL learning model has a significant influence on critical and creative thinking skills when compared to the conventional model in making dream house electrical circuits compared to the conventional model. The research results showed that there was a significant increase in critical and creative thinking skills in the experimental class compared to the control class. Data analysis using the t test showed that the posttest average score for students' critical and creative thinking skills in the experimental class was significantly higher than the control class. This research recommends the application of the PjBL learning model as an alternative learning method to improve the quality of education in elementary schools.